The Response of Simulated Arctic Mixed‐Phase Stratocumulus to Sea Ice Cover Variability in the Absence of Large‐Scale Advection. Issue 22 (22nd November 2017) - Li, Zhujun; Xu, Kuan‐Man; Cheng, Anning
Abstract: This study examines the responses of Arctic mixed‐phase stratocumulus boundary layer to sea ice cover variability near the sea ice margins using large eddy simulations. The simulations are conducted for two different atmospheric conditions, based on observations from the Surface Heat Budget of the Arctic Ocean Experiment (SHEBA) (100% sea ice‐covered) and the Mixed‐Phase Arctic Cloud Experiment (M‐PACE) (open ocean). The effect of sea ice cover variability is investigated for both atmospheric conditions by conducting a series of simulations prescribed with varying amounts of sea ice cover and no large‐scale advection. As sea ice cover amount decreases, the SHEBA boundary layer deepens and becomes decoupled. The relative strength of turbulence driven by surface heating to that driven by cloud top radiative cooling increases. Cloud ice and snow grow more efficiently than cloud liquid with moisture transported from the lower boundary layer. On the other hand, as sea ice cover amount increases, the M‐PACE boundary layer becomes shallower and more coupled with the surface as turbulence mainly driven by cloud top radiative cooling. Moisture supply from the surface is reduced, while cloud droplets are generated from turbulence at cloud top with little ice formation. In both atmospheric conditions, the boundary layer turbulence structure is modified according to change in the relative strength of boundary layer turbulent sources as sea ice amount changes, resulting in the growth/decay of the cloud layer. Simulations with smaller sea ice cover amounts are associated with more cloud ice but not necessarily more cloud liquid. Key Points: LES simulations are used to study the cloud topped boundary layer responses to sea ice cover variability near the sea ice margin area Change of sea ice cover amount modifies the relative strength of turbulent sources and the upward advection of water vapor into the clouds Simulations with smaller sea ice cover amounts are associated with more cloud ice but not necessarily more cloud liquid